Grotthuss mechanisms: from proton transport in proton wires to bioprotonic devices. (11th December 2015) - Miyake, Takeo; Rolandi, Marco
Abstract: In 1804, Theodore von Grotthuss proposed a mechanism for proton (H + ) transport between water molecules that involves the exchange of a covalent bond between H and O with a hydrogen bond. This mechanism also supports the transport of OH − as a proton hole and is essential in explaining proton transport in intramembrane proton channels. Inspired by the Grotthuss mechanism and its similarity to electron and hole transport in semiconductors, we have developed semiconductor type devices that are able to control and monitor a current of H + as well as OH − in hydrated biopolymers. In this topical review, we revisit these devices that include protonic diodes, complementary, transistors, memories and transducers as well as a phenomenological description of their behavior that is analogous to electronic semiconductor devices.